Representasi Adegan LGBT+ Pada Film Lightyear dan Zootopia Milik Disney - Siregar, Arvin Yogi (Universitas Muhammadiyah Sumatera Utara, 2025)
Animated films are a form of media that is very popular with various groups, especially children and teenagers. Apart from being entertainment, animated films can also be a means of education and the formation of social values in daily life. This study aims to analyze the representation of LGBT+ scenes in two animated films produced by Disney, namely Lightyear and Zootopia, using Roland Barthes' semiotic approach. Animated films have an important role not only as entertainment, but also as a medium for shaping social values and identities. This study aims to analyze the representation of LGBT+ scenes in two animated films produced by Disney, namely Lightyear and Zootopia, using Roland Barthes' semiotic approach. Animated films have an important role not only as entertainment, but also as a medium for shaping social values and identities. Lightyear features explicit LGBT representation through the character of Captain Alisha Hawthorne who has a same-sex partner and is portrayed as building a family. Instead, Zootopia presents an implicit representation of LGBT through the characters of Bucky and Pronk Oryx-Antlerson who are positioned as same-sex couples. The analysis is carried out through three levels of Barthes' meaning: denotation, connotation, and myth. The results show that at the level of denotation, films show literal scenes about same-sex relationships; at the level of connotation, the scene communicates the social meaning of equality, diversity, and normalization of LGBT identity; Meanwhile, at the mythical level, the film builds an ideological narrative that the ideal modern society is inclusive and multicultural. The findings also confirm that Disney used a different representation strategy: explicit in Lightyear to emphasize progressivity, and implicit in Zootopia as a careful strategy in dealing with global market sensitivities. This research is expected to contribute to the study of communication, especially the study of media representation, as well as to enrich the literature on the relationship between children's media, gender, and popular culture